Viability and oxidative stress of dental pulp cells after indirect application of chemomechanical agents: An in vitro study - Lins-Candeiro, Caio Luiz; Paranhos, Luiz Renato; de Oliveira Neto, Nilson Ferreira; Ribeiro, Rafael Antônio Oliveira [UNESP]; de-Souza-Costa, Carlos Alberto [UNESP]; Guedes, Fernanda Rodrigues; da Silva, Washington Henrique Themoteo; Turrioni, Ana Paula; Santos Filho, Paulo César de Freitas (Wiley, 2024)
Aim: This study evaluated the transdentinal cytotoxic effects of enzymatic agents (EA) for chemomechanical carious tissue removal on human dental pulp cells. Methodology: The groups were based on the performed dentine treatments (n = 8): G1: Positive Control (PC - no treatment); G2: Negative Control (NC - 35% H2O2 for 2 min); G3: Brix 3000™ (BX) for 30 s; G4: BX for 2 min; G5: Papacarie Duo™ (PD) for 30 s; G6: PD for 2 min. The cells were evaluated for viability (VB; MTT assay) and production of reactive oxygen species (ROS; DCFH-DA assay) and nitric oxide (NO; Griess reagent). A scanning electron microscope provided morphological chemical analyses and energy-dispersive X-ray spectroscopy. The data were submitted to the one-way anova statistical test complemented by Tukey (p <.05). Results: Cell viability decreased by 21.1% and 58.4% in G5 and G6, respectively. ROS production in G3 and G4 maintained basal levels but increased by 171.2% and 75.1% in G5 and G6, respectively. Conclusions: The Brix3000™ enzymatic agent did not cause indirect cytotoxic effects on pulp cells, regardless of the application time. Conversely, Papacarie Duo™ reduced viability and increased ROS production by pulp cells.
Keywords: cell survival; dental caries; dental materials; dental pulp; free radicals